Jones-matrix diagnostics of the structure and classification of optical properties inherent to birefringent polycrystalline networks of human biological tissues - Ushenko, O.G.; Balanetska, V.O.; Zabolotna, N.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Performed in this work is the complex statistical, correlation and fractal analysis of coordinate distributions of Jones-matrix elements corresponding to birefringent networks of liquid crystals in human biological liquids (saliva, blood plasma, bile). The authors have determined the values and ranges for changing statistical, correlation and spectral moments of the 1-st to 4-th orders that characterize Jones-matrix images of these objects. Ascertained are objective criteria for classification and differentiation of optical properties inherent to polycrystalline networks of biological crystals with various kinds of spatial symmetry: dendrite, spherolite and cluster ones.